The influence of leadership style, work environment and competency on employee performance: job satisfaction as an intervening variable at the Labour and Transmigration Office in the Province of Riau Islands - Alfian, Dedi; Wibisono, Chablullah; Khaddafi, Muammar (Journal of Multidisciplinary Academic and Practice Studies, 2024)
Purpose: This study aimed to analyze the effect of Leadership Style, Work Environment, and Competence on Employee Performance through Job Satisfaction as an intervening variable at the Riau Islands Provincial Manpower and Transmigration Office, totaling 105 employees of the Riau Islands Provincial Manpower and Transmigration Office. Methodology: The research method uses a quantitative approach with partial least squares (PLS) analysis techniques using SmartPLS version 4.0. Results: The results show that Leadership Style and Work Environment have a positive but insignificant effect on Employee Performance, while Competence and Job Satisfaction have a positive and significant effect. Furthermore, Leadership Style, Work Environment, and Competence have a positive and significant effect on Job Satisfaction. Job Satisfaction does not mediate the effect of Leadership Style on Performance, but it does mediate the effects of Work Environment and Competence on Employee Performance. Conclusions: Competence is a direct driver of employee performance, whereas Leadership Style and Work Environment exert their influence indirectly through Job Satisfaction. Enhancing job satisfaction can significantly improve performance. Limitations: This study was limited to one government office in a specific province, which may affect the generalizability of the findings. The use of self-reported data may also introduce biases. Contribution: This study contributes to the public sector human resource development literature by identifying key factors that influence employee performance and highlighting the mediating role of job satisfaction.